2016
DOI: 10.1016/j.nedt.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Specialty Practice Program characteristics and professional development outcomes

Abstract: The target participants, duration and clinical preparation of Transition to Specialty Practice Programs participants varied, impeding workforce mobility and articulation to postgraduate study and there were no professional development advantages from longer programs. There is an urgent need for a nationally consistent, evidence-based and fiscally responsible approach to Transition to Specialty Practice Programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recent research measures successful transition through reports of increased confidence, demonstrated competence, patient safety, organizational support, effective communication and leadership, and professional satisfaction (Barnes, 2015; Dillon et al, 2016). Unsuccessful transition can be reported as lack of confidence, negative emotions, poor patient care, or demonstration of skills, dependent practice, and poor retention (Barnes, 2015; Morphet et al, 2016; Widney & Cullen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research measures successful transition through reports of increased confidence, demonstrated competence, patient safety, organizational support, effective communication and leadership, and professional satisfaction (Barnes, 2015; Dillon et al, 2016). Unsuccessful transition can be reported as lack of confidence, negative emotions, poor patient care, or demonstration of skills, dependent practice, and poor retention (Barnes, 2015; Morphet et al, 2016; Widney & Cullen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that psychiatric nurses had fear over communicating with patients and attending psychiatric wards [12]. Patients' irritability and aggressiveness coupled with nurses' perceived inadequacy in dealing with such patients results in fear and stress [33][34][35]38].. Whilst nurses on other wards mostly fear committing errors or causing injuries to patients, participants in this study reported their greatest fears centered around patient assaults. Nursing students also fear attending psychiatric wards because they may believe that patients with psychiatric disorders are dangerous.…”
Section: Discussionmentioning
confidence: 95%
“…In the USA, the Emergency Nurses Association (ENA) identified that RENs were not being encouraged to complete a formal qualification or postgraduate certification in paediatric nursing to improve care 38 by some employers. It is worth noting that it has already been identified that rural hospitals within the USA have fewer Bachelor of Nursing qualified staff, as well as fewer nursing staff quotas in their emergency departments compared with other countries such as Australia 11,39 . This is a challenge that requires attention if rural nurses are expected to complete postgraduate qualifications in emergency nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…At an academic institution level, the provision of microcredentialling courses designed for RENs in paediatric emergency nursing could be created. It has been identified there is value in the provision of locally-focused learning packages, with enhanced teaching spaces and internet availability for videoconferencing between hospital and facility as a point of reference to support contextually relevant situations 39 .…”
Section: Recommendationsmentioning
confidence: 99%